Pengaruh Komitmen Organisasi, Disiplin Kerja dan Beban Kerja terhadap Kinerja Karyawan dengan Kepuasan Kerja sebagai Variabel Intervening: (Studi Kasus pada UD Udang Muncul Jaya Kabupaten Brebes) - Septa Wigo Lisnandiyanto; Slamet Bambang Riono; Hendri Sucipto; Azizah Indriyani (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to examine the effects of organizational commitment, work discipline, and workload on employee performance and job satisfaction at UD Udang Muncul Jaya in Brebes Regency. It also investigates the role of job satisfaction as an intervening variable between these factors and employee performance. Using a quantitative approach with Structural Equation Modeling Partial Least Squares (SEM-PLS), the study surveyed all 75 employees as the sample through a saturated sampling technique. Primary data was collected via questionnaires. The results indicate that work discipline and workload have a positive and significant effect on employee performance, while organizational commitment does not have a significant impact. Work discipline negatively and significantly affects job satisfaction, whereas organizational commitment and workload have no significant effect. Job satisfaction also negatively and significantly influences employee performance. Furthermore, job satisfaction does not mediate the relationship between organizational commitment, work discipline, workload, and employee performance. These findings provide important insights for management to improve employee performance by managing work discipline and workload, while also considering job satisfaction factors.